2007
DOI: 10.1016/j.exer.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Induction of axon and dendrite formation during early RGC-5 cell differentiation

Abstract: The retinal ganglion cell (RGC)-like RGC-5 line can be differentiated with staurosporine to stop dividing, extend neurites, and increase levels of several ganglion cell markers. This allows study of regulation of neurite development on a single cell basis. However, it is unclear whether the neurites induced by differentiation have features characteristic of dendrites or axons. To address this question, RGC-5 cells were differentiated with staurosporine and then immunoblotted for microtubuleassociated protein 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
0
36
1
Order By: Relevance
“…This clone (AP-20) of a-MAP-2 antibody detects HMW isoforms of MAP2 on immunoblots from immature rat hippocampus (Jalava et al, 2007) and immortalized RGC progenitor line RGC-5 (Lieven et al, 2007;Wood et al, 2010). In control adult retinal lysate (6-week-old retina), we observed a band of the expected size (control lane: mouse IgG) upon immunoblot analysis ( Supplementary Fig.…”
Section: Antibody Characterizationmentioning
confidence: 84%
“…This clone (AP-20) of a-MAP-2 antibody detects HMW isoforms of MAP2 on immunoblots from immature rat hippocampus (Jalava et al, 2007) and immortalized RGC progenitor line RGC-5 (Lieven et al, 2007;Wood et al, 2010). In control adult retinal lysate (6-week-old retina), we observed a band of the expected size (control lane: mouse IgG) upon immunoblot analysis ( Supplementary Fig.…”
Section: Antibody Characterizationmentioning
confidence: 84%
“…STSN represents a reliable agent to induce neuronal differentiation of RGC-5. The most commonly used protocol is 316 nM STSN in normal growth medium for usually 24 h, which can be extended for up to 5 days [10,18,24].…”
Section: Staurosporinementioning
confidence: 99%
“…The main finding of the present study is that staurosporine even at 50 nM, which is the lowest concentration that led to RGC-5 cell differentiation in our settings, induces apoptosis Since the publication of Frassetto et al [5] in 2006, which demonstrated that staurosporine differentiates RGC-5 cells to cells with numerous neuronal properties, in the absence of apoptosis induction, staurosporine has been considered to be the agent of choice to differentiate RGC-5 cells [4,[7][8][9].…”
Section: Discussionmentioning
confidence: 78%
“…Later on, the group of Levin [7] published that only a minor percentage of RGC-5 cells would be propidium iodide (PI)-positive, indicative for death, when cultured for 120 h with a staurosporine concentration of 316 nM. Since then, staurosporine has become the agent of choice for differentiating RGC-5 cells at a concentration of 316 nM for 24 h [7][8][9].…”
Section: Introductionmentioning
confidence: 98%